THE INFLUENCE OF MATHEMATIC COMMUNICATION ABILITY TOWARDS MATHEMATICS LEARNING ACHIEVEMENTS OF STUDENTS OF CLASS IX SMP NEGERI 8 TARAKAN - Irmawati Irmawati; Setia Widia Rahayu; Hermansyah Hermansyah (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2021)
The present study was a quantitative research with a survey method conducted in class IX of SMP Negeri 8 Tarakan. The objective of this study was to determine the effect of mathematical communication ability towards mathematical learning achievement of class IX student of SMP Negeri 8 Tarakan. This study was conducted in the even semester of the 2020/2021 academic year. There were 134 students who were taken using simple random sampling technique. The data were collected by distributing quetionnaire, mathematical communication ability test, and document of mathematical learning achievement. The data abtained were processed by using statistical data processing program, namely, SPSS version 23.0. The result of this study indicated that there was a partially significant effect of mathematical communication ability towards mathematical learning achievement of class IX students of SMP Negeri 8 Tarakan with the regression equation = 26.760 + 0.714 X. Based on the calculation of the coefficient determination, it was found that mathematical communication ability had an effect of 56.3% towards the mathematical learning achievement of class IX student of SMP Negeri 8 Tarakan.